先化简 再求值(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y) 其中x=-2,y=-1.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 01:08:00
先化简再求值(x-2y)(2y-x)+(2x+y)(2x-y)-(x-2y)(2x+y)其中x=-2,y=-1.先化简再求值(x-2y)(2y-x)+(2x+y)(2x-y)-(x-2y)(2x+y)
先化简 再求值(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y) 其中x=-2,y=-1.
先化简 再求值(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y) 其中x=-2,y=-1.
先化简 再求值(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y) 其中x=-2,y=-1.
解
(x-2y)(2y-x)+(2x+y)(2x-y)-(x-2y)(2x+y)
=(2xy-x²-4y²+2xy)+(4x²-y²)-(2x²+xy-4xy-2y²)
=(-x²-4y²+4xy)+(4x²-y²)-(2x²-3xy-2y²)
=(-x²+4x²-2x²)+(4xy+3xy)+(-4y²-y²+2y²)
=x²+7xy-3y²
=4+7×(-2)×(-1)-3×1
=4+14-3
=15
(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y)
=-(x^2-4y^2)+4x^2-y^2-(2x^2-3xy-2y^2)
=x^2+3xy+5y^2
中x=-2,y=-1
则原式=4+3x2+5x1
=15
(x-y)^2+7(x+y)-11(x-y)^2-8(x+y),先化简.再求值
先化简,再求值:y(x+y)+(x+y)(x-y)-x^2,其中x=-2,y=-1/2.
先化简,再求值:y(x+y)+(x+y)(x-y)-x²,其中x=-2,y=1/2.
先化简 再求值(x-2y)(2y-x)+(2x+y)(2x-y )-(x-2y)(2x+y) 其中x=-2,y=-1.
先化简,再求值:y(x-y)-x(x+y)/x²-y²÷x²+y²/x+y,其中x=2,y=-1
y(x+y)-(2x+y)(x-y)-x的2次方,其中x=-2,y=2分之1(先化简,再求值)先化简,再求值
先化简,再求值:【(x-y)^2+(x+y)(x-y)】/2x,其中x=2011,y=2010
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
先化简,再求值(-2y-x)(+2y-x)-(x+2y)^2,其中x=1,y=2
先化简,再求值:(x^2+y^2)(x-y)+2xy(x-y),其中x=-2,y=-3
先化简,再求值:(3x-y)²+(3x+y)(3x-y),其中x=1,y=-2
先化简,再求值 :x+y分之x²-y²-2(x+y),其中x=3,y=-三分之一
先化简,再求值:(x+3y)^2-(x+3y)(x-3y),其中x=3,y=-2.
先化简,再求值 [2/3x - 2/x+y(x+y/3x -x-y)]*x/x-y,其中5x+3y=0
先化简,再求值[(2x+y)^2-(2x+y)(2x-y)-y(5x+y)]÷(1/2y),其中x-y=2
先化简,再求值:[3x-2/x+y(x+y/3x-x-y)]/(x-y/x),其中5x+3y=0
先化简,再求值:[(x+y)(x-y)-(x-y)^2+2y(x-3y)]/(-4y),其中x=1,y=-2
先化简,再求值:[(x+y)(x-y)-(x-y)²+2y(x+y)]除4y,其中x=2,y=1